Information technology, inequality and adult literacy in developing countries - Simplice Asongu; Nicholas M. Odhiambo; Mushfiqur Rahman (African Governance and Development Institute (AGDI), 2023)
The study assesses linkages between information technology, inequality and adult literacy in 57 developing countries for the period 2012-2016. Income inequality is measured with the Gini coefficient while six dynamics of information technology are taken on board, namely: use of virtual social network, internet access in schools, internet penetration, mobile phone penetration, fixed broadband subscription and number of personal computer users. The findings show that only internet access in schools unconditionally promote adult literacy. The corresponding inequality threshold that should not be exceeded in order for internet access in schools to continue promoting adult literacy is 0.739 of the Gini coefficient. Policy implications are discussed.
Keywords: D10; D14; D31; D60; O30; 330; information technology; inequality; adult literacy